“Buy Now or Be Left Behind!”: How Does Social Media Marketing, Celebrity Endorsement, Peer Pressure, and Testimonial Affect Online Impulse Buying Behaviour? - Alawiah, Rani; Suthia Hayu, Rina (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
The states of social commerce development in Indonesia, especially TikTok Shop, has brought significant changes in the shopping patterns of Generation Z (Gen Z). This study evaluates the influence of social media marketing, celebrity endorsement, peer pressure, and user-generated content (UGC) on Gen Z's online impulse shopping behavior. A quantitative approach was used with purposive sampling technique on 474 Gen Z respondents who actively shop at TikTok Shop. Data analysis was conducted through Structural Equation Modelling (SEM) using SmartPLS. The results indicate that all four factors had a significant positive impact on impulse purchases, with peer pressure as the most dominant factor, followed by UGC, social media marketing, and celebrity endorsement. These findings confirm that social interaction, peer influence, and the authenticity of UGC play an important role in driving Gen Z's impulsive shopping decisions. From a practical perspective, marketers are advised to create strategies that take advantage of social pressures, such as group buying features, as well as work with micro-influencers to increase consumer trust. UGC based campaigns, such as creative challenges or user experience uploads, can increase audience engagement. Additionally, TikTok's recommendation algorithm can be optimized to display product content that matches Gen Z trends and preferences.